Hypertension in Women - Tasić, Tatjana; Tadić, Marijana; Lozić, Maja (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is one of the main causes of morbidity and mortality in the human population. Nevertheless, the intricate network of pathophysiological mechanisms that lead to the development of hypertension in women still awaits to be fully understood. From young age to maturity and senescence, the female body transits through different stages, each of them characterized with specific physiological features and disposition to particular pathological conditions, and that is exactly what makes the understanding of the genesis and adequate treatment of hypertension in women so challenging. Clinical and experimental findings emphasize the role of sex hormones, autonomic nervous system, renin-angiotensin-aldosterone system and arterial stiffness in the development of chronically elevated blood pressure in females. The purpose of this review is to briefly summarize the knowledge of the mechanisms and treatment of hypertension in women.